The midday sun reveals what the waters hide: Podocnemis unifilis Troschel, 1848 (Testudines, Podocnemididae), another exotic species in the Pantanal of Mato Grosso state - Silva, Odair Diogo da; Silva, Joselaine Souto Hall; Silva-Alves, Vancleber Divino; Costa, Thatiane Martins da; Fermiano, Eder Correa; Muniz, Claumir César; Ignácio, Áurea Regina Alves; Carniello, Maria Antonia; Vênere, Paulo César; Santos Filho, Manoel dos; et al. (Biota Neotropica, 2022)
Abstract The process of exotic species introduction is recognized as one of the greatest threats to the ecology and economy of the planet, due to changes in interactions in native biological communities. In this sense, reporting bioinvasions is the first step to understanding its introduction process and creating strategies to mitigate possible socio-environmental damages. Here we report the first records of Podocnemis unifilis introduced in the Northern Pantanal, Mato Grosso, Brazil. We obtained the species’ first records occasionally during 2014 and 2015. In the following years from 2016 to 2019, we carried out systematic observations through nautical incursions on the Paraguay River, between the Sepotuba River mouth and the Taiamã Ecological Station (TES). We also included third part records, when it was possible to prove the species identification and registration sites. Podocnemis unifilis adults, hatchling and nests were recorded at different points along the Paraguay River. Our results indicate that P. unifilis was introduced close to the urban nucleus of Cáceres about 30 years ago. Currently, it has an established population, recording nests and hatchling for years in a row. A particular one is its occurrence at the TES, an important natural fish nursery and refuge for the wetland fauna. Thus, continuous monitoring is suggested from P.unifilis, since the Pantanal’s environment with several different aquatic environments, offers favorable conditions for the species population increase in the Northern Pantanal.